PENGARUH KEBERADAAN AGROWISATA TAMAN AIR PERCUT TERHADAP SOSIAL EKONOMI MASYARAKAT (STUDI KASUS: DESA TANJUNG SELAMAT, KEC. PERCUT SEI TUAN, KAB. DELI SERDANG, SUMATERA UTARA) - Indah Dewi Permata; Yusniar Lubis; Azwana Nst (Jurnal Agriuma, 2021)
The purpose of this study was to determine the effect of the existence of Percut Water Parkagrotourism on the socio-economic community in Tanjung Selamat Village, Kec. Percut Sei Tuan, Kab. Deli Serdang, North Sumatra. Sampling was carried out using the Slovin formula. The sample in this study was the people of Tanjung Selamat Village with a sample of 75 respondents. The data collected are primary data and secondary data. The analytical method used is simple linear regression. The results showed that the existence of Percut Water Park. Agrotourism had an influence on the socio-economic community of Tanjung Selamat Village. The development of the Percut Water Parkagrotourism area improves the socio-economic conditions of the surrounding community. This can be seen from the emergence of business opportunities, employment, and increased income of the surrounding community. Percut Water Parkagrotourism has no effect on the sociocultural of the local community. The community still carries out social and religious activities before and afterPercut Water Park agrotourism.